The Effect of Social Media on Complex Buying Behavior in Insurance Industry with Age as Moderating Variable - Azman, Siti Nur Fadilah; Mohamad, Siti Hajar (Communica : Journal of Communication, 2025)
The increasing popularity of social media has provided a new opportunity for businesses to boost sales. The slow growth of insurance penetration rate in Malaysia, leaves many Malaysians at financial risk. Hence understanding how social media can affect complex buying behavior should help insurance companies to boost their sales. This study will focusing in Klang Valley population, since it is diverse in term of race, financial status and religion making it a suitable sample.  This study is using theory of Reasoned Action and Social Identity Theory to investigate how social media can give effect on complex buying behavior in insurance industry with age as moderating factor. The methodology used in this study is online survey, it was designed and distributed to target respondents in Klang Valley using purposive sampling. A total of 211 responses were gained and only 178 from them are valid responses. The responses were analyzed with SPSS and Partial Least Square structural equation modeling (PLS-SEM). The finding of the study discuss both user review and social proof were discovered to have significant influence on complex buying behavior in insurance industry. However social media influencer does not significantly affect complex buying behavior. Furthermore, it was also found that age does not moderate the relationship between user review and complex buying behavior in insurance industry. The results contribute to the academic literature by reinforcing the relevance of TRA and SIT in understanding consumer decision-making in complex purchases.